Stem Cell Therapy to Restore Pancreatic Function in Dogs and Cats - Will, Sonia E. A. L.; Morini Júnior, João C.; Alcântara, Dayane; Fratini, Paula; Favaron, Phelipe O.; Miglino, Maria Angélica; Assis Neto, Antônio C. (Brazilian Journal of Veterinary Pathology, 2012)
Diabetes mellitus is a common disease in dogs and cats. It consists of a group of metabolic diseases characterized by hyperglycemia resulting from defects in secretion and/or insulin activity. The islets of Langerhans from donor pancreas may be an alternative for the cure of diabetes, however, this approach is limited because the donation is scarce and complications occur due to the concurrent use of immunosuppressive drugs. For many decades researchers have sought ways to replace pancreatic islets in diabetic individuals. Current studies in progress with stem cell culture for production of pancreatic islet cells are promising, despite the difficulties in their production. This review reports several aspects concerning the use of stem cells in diabetes cell therapy. Recent studies in mice have shown that embryonic stem cells can be induced to differentiate into insulin-producing β-cells. In parallel with this study, a new class of stem cells has emerged, i.e. induced pluripotent stem cells (iPSCs) aimed at clinical and therapeutic use. Adult stem cells may circumvent the ethical issues surrounding embryonic stem cells and allow auto-transplantation.